Use of Ginseng in Medicine With Emphasis on Neurodegenerative Disorders - Khaled Radad; Gabriele Gille; Linlin Liu; Wolf-Dieter Rausch (Elsevier, 2006)
Abstract.: Ginseng, the root of Panax species, is a well-known herbal medicine. It has been used as a traditional medicine in China, Korea, and Japan for thousands of years and is now a popular and worldwide used natural medicine. The active ingredients of ginseng are ginsenosides which are also called ginseng saponins. Recently, there is increasing evidence in the literature on the pharmacological and physiological actions of ginseng. However, ginseng has been used primarily as a tonic to invigorate week bodies and help the restoration of homeostasis. Current in vivo and in vitro studies have shown its beneficial effects in a wide range of pathological conditions such as cardiovascular diseases, cancer, immune deficiency, and hepatotoxicity. Moreover, recent research has suggested that some of ginseng's active ingredients also exert beneficial effects on aging, central nervous system (CNS) disorders, and neurodegenerative diseases. In general, antioxidant, anti-inflammatory, anti-apoptotic, and immune-stimulatory activities are mostly underlying the possible ginseng-mediated protective mechanisms. Next to animal studies, data from neural cell cultures contribute to the understanding of these mechanisms that involve decreasing nitric oxide (NO), scavenging of free radicals, and counteracting excitotoxicity. In this review, we focus on recently reported medicinal effects of ginseng and summarize the current knowledge of its effects on CNS disorders and neurodegenerative diseases. Keywords:: ginseng, ginsenoside, central nervous system, herbal medicine, Chinese herb